Avaliação da Exposição à Radiação no Médico Intervencionista em Procedimentos no Setor de Hemodinâmica - Bacchim Neto, Fernando Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Interventional Radiology (IR) is the area of radiology that provides the highest doses of radiation for medical staff. Studies show that personal dosimeters may underestimate doses in OEI, especially in the extremities (hands and feet) and in the eye lens. The aim of this study was to investigate the radiation exposure profiles in medical staff during different interventional procedures in Hemodynamics Service, Botucatu Medical School. among all procedures we choose: angiography, angioplasty, with or without stents fixation and angioplasty with endoprothesis fixation (in case of stroke kind aneurysms). The groups were designated: diagnosis, angioplasty and aneurysms treatment, respectively. In each evaluation procedures, dosimeters were placed at the primary interventional radiologist and at one assistant who remained in the room throughout the procedure. Dosimeters were fixed at the following locations: a few inches below the eye lens (on top of the surgical mask), thyroid, chest, gonads, hand (bottom of the pulse) and foot, above the radiological protection vests as lead apron and thyroid shield. 23 procedures were evaluated: 10 diagnostics, 9 angioplasty and 4 aneurysm treatment. For diagnostic and angioplasty categories, the highest dose values per procedure for main interventionist, were in the region of gonads (227.2 ±201.9 μSv and 209.6 ±109.5 μSv respectively) for assistant interventional, were in the region of the feet (93.2 ±78.7 μSv and 69.9 ±47.8 μSv respectively). In the procedures of endoprothesis type, for both the main interventionist as to the assistants, the highest dose values were for the regions of the gonads (1894.5 ±1131.5 μSv and 1818 ±1521.1 μSv respectively). Based on the exposure profiles of each type of exam, the number of procedures that can be performed without the current reference levels are exceeded, both the main interventionist and for the assistant were estimated. The maximum number of annual...

A Radiologia Intervencionista (RI) é a área do radiodiagnóstico que proporciona os maiores valores de dose para a equipe médica. Estudos mostram que os dosímetros pessoais podem subestimar os valores de dose nos médicos intervencionistas, principalmente nas extremidades e nos cristalinos, dificultando a análise dos riscos envolvidos com os procedimentos intervencionistas para a equipe médica. O objetivo do presente estudo foi investigar os perfis de exposição à radiação da equipe médica durante diferentes procedimentos intervencionistas no Setor de Hemodinâmica do Hospital das Clínicas da Faculdade de Medicina de Botucatu (HC-FMB). Foram selecionadas três categorias de procedimentos: angiografias, angioplastias, com ou sem fixação de stents e angioplastias com fixação de endopróteses (no caso de acidentes vasculares do tipo aneurismas). Os grupos foram denominados: diagnóstico, angioplastia e endoprótese, respectivamente. Para cada procedimento, foram colocados dosímetros no médico intervencionista principal e em um assistente nos seguintes locais: alguns centímetros abaixo dos cristalinos, tireoide, tórax, gônadas, mão e pé. Os dosímetros foram fixados sobre a superfície destas estruturas inclusive acima das vestimentas de proteção radiológica. Ao todo foram avaliados 23 procedimentos, sendo 10 diagnósticos, 9 angioplastias e 4 endopróteses. Para as categorias diagnóstico e angioplastia, os maiores valores de dose por procedimento, para os intervencionistas principais, foram na região das gônadas (227,2 ±201,9 μSv e 209,6 ±109,5 μSv respectivamente) para os intervencionistas assistentes foram na região dos pés (93,2 ±78,7 μSv e 69,9 ±47,8 μSv respectivamente). Nos procedimentos do tipo endoprótese, tanto para os intervencionistas principais quanto para os assistentes, os maiores valores de dose foram para as regiões das gônadas (1894,5 ±1131,5 μSv e 1818 ±1521,1 μSv respectivamente). Com...
Keywords: Exposição a radiação; Radiologia intervencionista; Exposição ocupacional; Occupational Exposure; Radiation Exposure